Trend 1980 - 2011. Energy Information Administration. International Energy Statistics: Total Primary Energy Consumption | Country: Greenland | Indicator: Total Primary Energy Consumption (Quadrillion Btu), 1980-2011. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 004-014-038. - Energy Information Administration (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Energy Information Administration (2015). International Energy Statistics: Total Primary Energy Consumption | Country: Greenland | Indicator: Total Primary Energy Consumption (Quadrillion Btu), 1980-2011. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 004-014-038. Dataset: Provides statistics on total primary energy consumption by country, as available. Total primary energy consumption includes the consumption of petroleum, dry natural gas, coal, and net nuclear, hydroelectric, and non-hydroelectric renewable electricity. Total primary energy consumption for each country also includes net electricity imports (electricity imports minus electricity exports).Total primary energy consumption for the United States also includes the consumption of biomass, geothermal, and solar energy not used for electricity generation. Total primary energy consumption per capita is calculated by dividing the data on total primary energy consumption in quadrillion British thermal units (Btus) for each country and year by the population in millions for each country and year. The dataset provides data for 220 countries, as available, on energy-related metrics, including total and crude oil production, oil consumption, natural gas production and consumption, coal production and consumption, electricity generation and consumption, primary energy, energy intensity, CO2 emissions and imports and exports for all fuels. Data are sourced from Energy Information Administration research, as well as from national and international agencies, listed at http://www.eia.gov/cfapps/ipdbproject/docs/sources.cfm. Category: Energy Resources and Industries, International Relations and Trade Source: Energy Information Administration The Energy Information Administration (EIA), created by Congress in 1977, is an independent statistical and analytical agency within the United States Department of Energy. Its mission is to provide policy-independent data, forecasts, and analyses to promote sound policy making, efficient markets, and public understanding regarding energy and its interaction with the economy and the environment. http://www.eia.doe.gov/ Subject: Energy Demand, Energy Consumption